If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + (5x + 9) = 0 Reorder the terms: 6 + (9 + 5x) = 0 Remove parenthesis around (9 + 5x) 6 + 9 + 5x = 0 Combine like terms: 6 + 9 = 15 15 + 5x = 0 Solving 15 + 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 5x = 0 + -15 Combine like terms: 15 + -15 = 0 0 + 5x = 0 + -15 5x = 0 + -15 Combine like terms: 0 + -15 = -15 5x = -15 Divide each side by '5'. x = -3 Simplifying x = -3
| An=7+(-6)(n-1) | | 8x+x=1000 | | 1x+1y=2xy | | 3mn+4m= | | P+6.3=2.7 | | 2x+x+4=2 | | -7x-(x+3)=1 | | 7(1-9x)=-28 | | 1/2=2/5c-3 | | 3x(x)=96 | | f(x)=-2x^3+5x-1 | | 4(6d+8)=-33 | | 6x-2+2x-5=9 | | 7[8-(-6x-5)]=84x+126 | | 7=8x+2 | | 2g-4=35 | | 4x+2y=-84 | | 2x^2+5x-250=0 | | 7x+3(3x+12)=132 | | -7=2n+36 | | -6a+7a=-31 | | 6.7=a+2.7 | | 10+3x=2(3+4x)+15 | | 3(x+4)-5x=9 | | -9x+7+3x=19 | | 32+7c=-3(8c+6) | | 98=-6x+32 | | xy-18+2y-9x=0 | | -7-a=a+3 | | 1x+2x+3x=13 | | 5x+3-2x=2 | | 4x^5-8x^4+16x^3= |